The Influence of Leadership Style on Ecological Behavior Mediated by Persistence and Integrity on the State Civil Apparatus of the Provincial Government of the Special Region of Jakarta - Hendayana, Taufik; Purwanto, Agung; Abbas, Hafid (IJBLE Scientific Publications Community Inc., 2024)
The results of the study show that leadership style has a significant direct influence on the ecological behavior of ASN. Inspirational and supportive leaders are able to increase ASN's commitment to environmentally friendly behavior. In addition, persistence and integrity have been shown to mediate the relationship. Leaders who are able to motivate ASN persistence and instill strong integrity values tend to be more effective in building sustainable ecological behavior. Persistence increases the ability of civil servants to survive in their efforts to implement ecological practices, while integrity encourages civil servants to act in accordance with ethical values in preserving the environment. In conclusion, an effective leadership style, with the support of persistence and integrity, can improve the ecological behavior of civil servants. These findings have important implications for the development of leadership policies that support environmental sustainability in the public sector, especially within the scope of the Jakarta Special Region Provincial Government.